Options of conservative treatment at acute adhesive smallintestinal obstruction - S. G. Shapovalyants; S. Ye. Larichev; M. Ye. Timofeyev; I. V. Babkova; Z. A. Zhemukhova; O. I. Seryogina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2013)
Aim of investigation. Improvement of management approach of patients with acute smallintestinal adhesive obstruction (ASIAO) based on choice of method and duration of conservative obstruction treatment.Material and methods. The study group included 516 patients with obturation form of ASIAO without indications for emergency surgery, who underwent conservative treatment. In 188 patients endoscopic nasointestinal decompression of gastro-intestinal tract was carried out. Due to inefficiency of therapy 269 patients were operated urgently. Original method of treatment efficacy prediction was developed in the clinic. Groups with low, medium and high probability of obstruction resolution were defined.Results. The group with resolved obturation ASIAO (n=247) average duration of conservative treatment was 11,4±4,8 h. In 92 patients results of conservative treatment prediction were determined at ASIAO (forecast effectiveness was 98,9%).Conclusions. The differentiated approach to choice of conservative actions and improvement of its terms have allowed to increase treatment response rate of obturation ASIAO to 66,3% and to decrease mortality to 2,2%.